2013
DOI: 10.1002/tox.21880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic, oxidative stress, proinflammatory and genotoxic effect of silver nanoparticles in human lung epithelial cells

Abstract: Silver nanoparticles are increasingly used in various products, due to their antibacterial properties. Despite its wide spread use, only little information on possible adverse health effects exists. Therefore, the aim of this study was to assess the toxic potential of silver nanoparticles (<100 nm) in human lung epithelial (A549) cells and the underlying mechanism of its cellular toxicity. Silver nanoparticles induced dose and time-dependent cytotoxicity in A549 cells demonstrated by MTT and LDH assays. Silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 39 publications
9
63
0
Order By: Relevance
“…Hence, the potential of AgEO-and AgCitrate-NP to trigger oxidative stress and subsequent DNA damage was analyzed in PBCEC and PCPEC. The potential of Ag-NPs to trigger oxidative stress and DNA damage has already been shown in many studies [5,20,29,34]. However, this has not yet been elucidated in barrier-forming cells of the CNS.…”
Section: Inflammatory Reaction In Pbcecmentioning
confidence: 99%
“…Hence, the potential of AgEO-and AgCitrate-NP to trigger oxidative stress and subsequent DNA damage was analyzed in PBCEC and PCPEC. The potential of Ag-NPs to trigger oxidative stress and DNA damage has already been shown in many studies [5,20,29,34]. However, this has not yet been elucidated in barrier-forming cells of the CNS.…”
Section: Inflammatory Reaction In Pbcecmentioning
confidence: 99%
“…The complementary advantages of the magnetic resonance imaging (MRI) and TPF in one nanoprobe can endow probes the ability of accurate positioning of the overall tumor in the body and the fine local details, which is attractive for the early diagnosis of tumors 6. Compared with the widely studied Au‐based NPs, Ag‐based NPs are seldom used in biomedical field, except for antimicrobial, mainly due to the serious cytotoxicity of Ag + released from Ag NPs 7. However, the unique properties of Ag NPs, such as special optical property, excellent electrical conductivity, good catalytic ability, bactericidal ability, and so on, are promising for biomedical application except their toxicity 8.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the cytotoxic effects of AgNPs on cancer cells, along with the noncytotoxic effects of AuNPs, were similar to our findings. 26,27,[29][30][31] Suliman et al reported 32 AgNPs show less cytotoxicity on A549 cell compared with D-AgNPs at same concentration. Next, the synergistic effect between Dendropanax nanoparticles (silver and gold) and the ginsenoside CK was determined.…”
Section: In Vitro Cytotoxicity Of D-agnps and D-aunps In Lung Cancer mentioning
confidence: 99%